Investigating the Academic Stress and Mental Well-Being Among Undergraduate Students After COVID-19 Pandemic Era - Anuar A.; Ibrahim Z.; Jamaluddin J.E. (Springer Science and Business Media Deutschland GmbH, 2025)
Stress has been identified to be detrimental to students? well-being especially during the COVID-19 pandemic. A descriptive cross-sectional online survey was conducted among undergraduate bachelor?s degree students at Universiti Tenaga Nasional (UNITEN) between December 16, 2022, and January 6, 2023. This study is aimed to investigate the level of perceived stress due to academic related activities after the pandemic. Descriptive statistical analysis was used to assess the levels of perceived stress among genders and different levels of study. A total of 338 students (55.03% male, 44.97% female) participated. Most students perceived themselves to be stressed (34.62% high stress, 50.62% medium stress) with academic related work. More female students (39,47%, n = 152) perceived themselves to experience high stress level compared to male students (30.65%, n = 182). The main factors causing stress are due to assessment (54.44%), subject difficulty (50.3%) and class schedule (30.77%). Perceived stress can have a major negative impact on a student?s mental wellbeing. It is important to identify students who experience a high amount of stress and take immediate suitable action to reduce the perceived stress. ? The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.